Maintenance Guide for Greenhouse Ventilation, Evaporative Cooling Heating Systems - D. E. Buffington; R. A. Bucklin; R. W. Henley; D. B. McConnell (EDIS)
Heating, cooling and ventilation are three main environmental control methods to maintain the desired growing environments. Regular maintenance of the equipment is the key to an effective performance. Any small changes or a minor downtime could reduce the overall efficiency of these systems which could lead to crop failure. This fact sheet will emphasize corrective and preventive maintenance procedures for ventilation, evaporative cooling and heating systems.